PERCEPTION OF REHABILITATION SERVICE FOR DRUG ABUSE TREATMENT IN ACEH, INDONESIA - Desi Rosdiana; Mustanir; Marthoenis; Marty Mawarpury. (RADJA PUBLIKA, 2025)
Drugs are importantly global problem that no single country alone could address, including Indonesia. National Narcotics Agency recorded 36,137 drug abuse patients in Indonesia in one decade. The aims of the study is to determine community perception of rehabilitation service for drug abuse treatment in Aceh Province. A type of descriptive analytic with a cross sectional study approach, the current research employs a questionnaire distributed online to 10 districts/cities in Aceh Province which has National Narcotics Agency representatives. Questionnaires in online form which began on 10 June 2022 and closed on 18 June 2022. The sample in this study has criteria for ≥18 years and is willing to be a respondent Involving 86 drug users. they are divided into two groups, rehabilitation patient (n=43) and those who have never used rehabilitation services (n=43). The questionnaire used has been tested for validity on 38 respondents. Using Mann-Whitney test with STATA application version 13.0. The study indicated that there were particularly perception differentiation of people who have participated in outpatient rehab for drug abuse with the perception of people who have never used rehabilitation services. (p=0,0084). In general, the community have a positive perception of rehabilitation services, 90.70% useful rehabilitation, 81.40% free rehabilitation, easy to get access into rehabilitation and it has easy procedures 81.40%, safe and comfortable rehabilitation centers 81.40%, information addicts are guaranteed to keep their privacy 88.37%, do not get stigma from the society 74.42%, and friendly and competent officers 87.21%. However, there is a negative perception that the community still doubt that undergoing rehabilitation for addicts will recover. (46.51%). Efforts to enhance the competence of rehabilitation officers and disseminate information about rehabilitation on a massive scale are necessary to be conducted by involving related sectors.